2014
DOI: 10.5539/ijbm.v9n9p41
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Governance Mechanisms and Auditor Choice: Evidence from China

Abstract: This paper provides empirical evidence on the association between corporate governance mechanisms and the choice of high-quality and low-quality auditors (hereafter "auditor choice") based on firm's data from Chinese listed firms between 2007 and 2012. Consistent with most literature, this paper adopts Big 4 auditors as the proxy for high-audit quality. Our findings indicate that certain corporate governance factors, ownership of the largest shareholders, the aggregate of ownership of other large shareholders,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…Empirically, Beasley and Petroni (2001) investigated the role of independent directors in the selection of external auditors in insurance companies and found that the likelihood of a firm employing a specialized, brand name auditor increased with the percentage of independent board members. Similarly, Leung and Cheng (2014) found that the percentage of independent directors on a board had a significant positive influence on auditor choice. In contrast, Aljabr (2010) failed to document a significant association between the presence of independent directors and auditor choice.…”
Section: Hypotheses Development 231 Board Independencementioning
confidence: 90%
“…Empirically, Beasley and Petroni (2001) investigated the role of independent directors in the selection of external auditors in insurance companies and found that the likelihood of a firm employing a specialized, brand name auditor increased with the percentage of independent board members. Similarly, Leung and Cheng (2014) found that the percentage of independent directors on a board had a significant positive influence on auditor choice. In contrast, Aljabr (2010) failed to document a significant association between the presence of independent directors and auditor choice.…”
Section: Hypotheses Development 231 Board Independencementioning
confidence: 90%
“…They report that firms subject to agency problems in the form of blockholder ownership are more likely to appoint Big 5 auditors to provide high audit quality. Leung and Cheng (2014) provide a similar result based on data from Chines listed firms. Yang et al (2019) reported that a company whose controller has foreign residency rights is more likely to choose a Big 4 auditor than other companies.…”
Section: Family Ownership and Auditor Choicementioning
confidence: 52%
“…Consistent with prior research, auditor size will be employed as a dependent (e.g. Leung et al, 2014;Leung and Liu, 2015;Darmadi, 2016;Kim et al, 2018, Yang et al 2019).…”
Section: Measurement Of Variables and Model Specificationmentioning
confidence: 99%
“…multiple large shareholders) but find mixed results. For instance, Leung and Cheng (2014) and Leung and Liu (2015) show that the aggregate ownership of the second to fifth largest shareholders has a significantly positive influence on Big Four auditor choice [8]. However, it has also been argued that in the Chinese setting, large shareholders may not prefer high-quality auditors because they can maximize their private benefits by expropriation from other shareholders without strong monitoring from high-quality auditors.…”
Section: Institutional Background Related Literature and Hypotheses D...mentioning
confidence: 99%